Advances in the application of N-sulfinyl auxiliaries to the synthesis of pyrrolidines and α-amino acid derivatives - O'Connor, Daniel (2020)
Pyrrolidines are widely prevalent in pharmaceuticals, catalysis and agrochemicals. The (3+2) cycloaddition of azomethine ylides with alkenes is one of the most powerful methods for pyrrolidine synthesis. This reaction creates 2 σ-bonds and up to 4 new stereocentres in one reaction. Methods for the stereoselective synthesis of pyrrolidines which possess functionality in the 2- and 5-positions have been extensively developed; however, methods for the stereoselective synthesis of pyrrolidines without substituents in the 2- and 5-position are sparse.